2016
DOI: 10.1186/s12889-016-3594-8
|View full text |Cite
|
Sign up to set email alerts
|

Why media representations of corporations matter for public health policy: a scoping review

Abstract: BackgroundMedia representations play a crucial role in informing public and policy opinions about the causes of, and solutions to, ill-health. This paper reviews studies analysing media coverage of non-communicable disease (NCD) debates, focusing on how the industries marketing commodities that increase NCD risk are represented.MethodsA scoping review identified 61 studies providing information on media representations of NCD risks, NCD policies and tobacco, alcohol, processed food and soft drinks industries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
72
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 61 publications
(66 reference statements)
1
72
0
1
Order By: Relevance
“…The social issues journalists decide to report on, and how they do so, can either bring issues to the spotlight or leave them out of public conversations and the consideration of policymakers [37]. For example, an analysis of media discourse on non-communicable disease (NCD) risks and policies found that, while corporations place a greater focus on individual responsibility and draw on market justice frames when discussing NCDs, public health advocates who contribute to news media were more inclined to frame their debates around social justice issues and promoted population-level interventions and structural change [29]. Market justice frames are oriented towards low obligation to the collective good, values of self-determination, and limited government intervention [38].…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…The social issues journalists decide to report on, and how they do so, can either bring issues to the spotlight or leave them out of public conversations and the consideration of policymakers [37]. For example, an analysis of media discourse on non-communicable disease (NCD) risks and policies found that, while corporations place a greater focus on individual responsibility and draw on market justice frames when discussing NCDs, public health advocates who contribute to news media were more inclined to frame their debates around social justice issues and promoted population-level interventions and structural change [29]. Market justice frames are oriented towards low obligation to the collective good, values of self-determination, and limited government intervention [38].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similar to the tobacco and alcohol industries, corporations representing fast food tend to have a uniform view on consumption of these products and related policies-which influence arguments made in the press to focus on unhealthy lifestyles, individual responsibility, consumer choice and economic arguments, leading consumption to be seen as a personal choice, an individual level responsibility and a moral issue [29]. Taken together, problematic consumption is typically blamed on the individual having a behavioural problem, rather than framing the issue as a structural societal problem.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The HPL not only affects potential SSB consumers by causing price increases, but news media coverage of the tax can inform consumers as to the tax's existence and purpose. News media can assist a public health intervention, through its ability to reach a wide public audience and second, through agenda setting, whereby news organizations control topic salience for the public and urgency for policy action through the frequency of news coverage (11)(12)(13)(14). By controlling the public's frequency of exposure to the topic, news media affect how important the topic is perceived to be by the public.…”
Section: Introductionmentioning
confidence: 99%